폴리아닐린 코팅을 통해 전자밀도가 향상된 NiFe-LDH의 산소 발생 반응 활성에 대한 고찰 - 김인태; In Tae Kim; 구태우; Taewoo Koo; 박현기; Hyeon Ki Park; 이우재; Woo-jae Lee; 김건휘; Geon Hwee Kim; 박범경; Beom-kyeong Park; et al. (대한금속·재료학회지, 63(8), 2025)
Water electrolysis is an efficient and environmentally friendly hydrogen production technology that emits no greenhouse gases. However, its overall efficiency is significantly constrained by the high overpotential associated with the oxygen evolution reaction (OER), and this remains the bottleneck in water splitting. Among various OER catalysts, NiFe-layered double hydroxide (NiFe-LDH) has emerged as a promising candidate due to its low cost and high intrinsic activity. Its catalytic performance, however, is limited by the strong binding of OH intermediates, which inhibits rapid reaction kinetics and restricts further improvements in efficiency. In this study, we designed and synthesized PANI@NiFe-LDH by coating polyaniline (PANI) onto the surface of NiFe-LDH to modulate its electronic structure and alleviate the adsorption strength of reaction intermediates. The intimate interfacial interaction between PANI and NiFe- LDH effectively redistributed the electronic density. This in turn optimized the OH adsorption energy and led to faster OER kinetics. As a result, the PANI@NiFe-LDH exhibited significantly enhanced catalytic activity compared to pristine NiFe-LDH. Furthermore, when applied as anode catalyst in an anion exchange membrane water electrolysis (AEM electrolyzer), PANI@NiFe-LDH demonstrated excellent performance under alkaline conditions, confirming its practical applicability in sustainable hydrogen production systems. This work not only demonstrates an effective strategy to improve the OER performance of non-platinum group metal (non-PGM) based catalysts but also provides insights into the role of polymer coatings in tuning the surface electronic structure for AEM electrolyzer. (Received 2 June, 2025; Accepted 17 June, 2025)